DIVERSITY OF YAM-BASED PRODUCTION SYSTEMS AND SUSTAINABLE SOIL MANAGEMENT: THE CASE OF TIÉNINGBOUÉ IN IVORY COAST - Esther OKA; Anne FLOQUET; Daouda DAO; Carmelle Ornélia HOUNNAKOUN; Roch L. MONGBO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Yams are cultivated by almost every household in Tiéningboué in the northern center of Ivory Coast. The steady increase in production by increasing the areas of cultivation leads to a scarcity of land, which commands for more sustainable management practices regarding soil fertility. This study establishes the baseline for more effective interventions of a research for development project 'YAMSYS’, aiming to develop more sustainable yams production systems. To assess the accumulation of natural and social capital that are essential factors in sustainable production systems, a typology combining qualitative and quantitative approach is developed. Then, stakeholder analysis is carried out for soil fertility management. Six yam-based production systems are identified: 'yam specialists’ (1%), 'cotton growers’ (15%), 'smallholders’ (47%), 'very large indigenous farms’ (3%), 'large indigenous farms’ (27%), 'large allochthonous and allogeneic non-cotton farms’ (7%). Results show both similarities and differences in production system, as well as predictions of reaction of the groups to Integrated Soil Fertility Management (ISFM) technologies developed by YAMSYS. For 'Smallholders’, facing low resource endowments, the potential for ISFM techniques adoption is the highest when their cropping system become permanent. Ultimately, the study highlights the stakeholders making up an innovation platform whose objective is to have “champions” along the yam value chains acting as “agents of change” allowing farmers to adapt new technologies for better management of soil fertility.